PERLINDUNGAN HUKUM HAK TERKAIT PRODUSER FILM WARKOP DKI REBORN ATAS PENAYANGAN SECARA LIVE STREAMING MELALUI APLIKASI VIDEO ONLINE BIGO LIVE - Devina Kaharu; Irta Windra Syahrial; Heru Susanto (CALYPTRA, 2018)
The advancement of technology and science provides an opportunity for the growing use of technology. The use of technology that is not based on the knowledge of a rule of law will lead to a violation, does not rule out the occurrence of copyright infringement that can provide harm to the creator. With the Internet network increasingly expanding the incidence of an infraction because it can be seen by the public. Bigo live is an online streaming video application that is used to broadcast users' self activities online through smartphone cameras and can be watched by other bigo live users at the same time. The action of a bigo live app user who has brodcast live at the premier of a movie is a copyright infringement. It has violated the economic rights of the author under Article 9 paragraph (1) letter b, Article 9 paragraph (3), and Article 20 Sub-Article c of the Copyright Law.